Lived Citizenship on the Edge of Society : Rights, Belonging, Intimate Life and Spatiality - Warming, Hanne; Fahnøe, Kristian (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This edited collection presents the concept of lived citizenship as a fruitful avenue for exploring the role played by social work practices in the lives of people in vulnerable positions. The book centres on the everyday experiences through which people practice, negotiate, understand and feel their citizenship. The authors offer both empirical analyses of how social work influences the rights, obligations, identities and belongings of children, homeless people, migrants, ethnic minorities, and young people with mental disabilities; and a theoretical framework for analysing the complexities of social work. Drawing on the notion of intimate citizenship and an understanding of citizenship as socio-spatial, the theoretical framework addresses the challenges of enhancing the agency of social work clients and of promoting inclusive citizenship, and how these challenges are shaped by emotions, affect, rationality, materiality, power relations, policies and managerial strategies.< Lived Citizenship on the Edge of Society will be of interest to students and scholars across a range of disciplines including social policy and social work. .
Keywords: Social sciences.; Social structure.; Social inequality.; Social policy.; elektronické knihy; electronic books